2015
DOI: 10.4103/0019-5049.162988
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of ultrasound-guided paravertebral block with ropivacaine versus bupivacaine for post-operative pain relief in children undergoing thoracotomy for patent ductus arteriosus ligation surgery

Abstract: Background and Aims:Thoracotomy incision following patent ductus arteriosus (PDA) ligation surgery is often associated with severe post-operative pain that has deleterious effects on respiratory function. We aimed to assess pain relief with thoracic paravertebral block using either bupivacaine or ropivacaine in these surgeries.Methods:One hundred paediatric patients of age group between 2 and 10 years undergoing PDA ligation surgery were randomised either to bupivacaine or ropivacaine group in this prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(24 reference statements)
2
4
0
Order By: Relevance
“…PVB significantly decreased intraoperative consumption of opioids compared to DSPB and SSPB, which indicated that the short-term analgesic effect of PVB was better than that of DSPB and SSPB. These findings support observations from previous reports that showed the effectiveness of PVB [24].…”
Section: Discussionsupporting
confidence: 93%
“…PVB significantly decreased intraoperative consumption of opioids compared to DSPB and SSPB, which indicated that the short-term analgesic effect of PVB was better than that of DSPB and SSPB. These findings support observations from previous reports that showed the effectiveness of PVB [24].…”
Section: Discussionsupporting
confidence: 93%
“…PVB signi cantly decreased intraoperative consumption of opioids comparing to DSPB and SSPB, which indicated the short-term analgesic effect of PVB was better than that of DSPB and SSPB. These ndings support observations from previous reports that showed the effectiveness of PVB (24).…”
Section: Discussionsupporting
confidence: 92%
“…Inadvertent vascular puncture in particular has been reported in 13 publications. [98][99][100][101][102][103][104][105][106][107][108][109][110] These were reported across a range of adult and pediatric populations, under anatomic and ultrasound guidance, during single shot and catheter blocks, and with rates in these reports of between one-in-527 102 and one-in-eight. 105 None of these cases resulted in serious bleeding outcomes, despite the presence of therapeutic anticoagulation in two reports.…”
Section: Paravertebral Blockmentioning
confidence: 99%